Steroid dari Kulit Batang Aglaia grandis (Meliaceae) - Kindi Farabi; Nurlelasari Nurlelasari; Siti Hani Pratiwi; Desi Harneti; Rani Maharani; Agus Safari; Unang Supratman (Al-Kimia, 2021)
Steroids are a group of secondary metabolite which showed various biological activities. Meliaceae is a plant family used as a one of the source of steroid compounds. A. grandis is a member of the Meliaceae family in genus Aglaia which rarely explored. Previous studies have shown that A. grandis leaves contain triterpenoids, steroids, bisamide, and sesquiterpenoids. This study aims to obtain steroids from the bark of A. grandis. The structure of the isolated compound was determined using the NMR 1D and 2 D spectroscopic. Based on the extensive analysis, isolated compound identified as a stigmastant type steroid, stigmast-5-en-3β-ol-7-one.